Eight perfect hours - Louis, Lia (Emily Bestler Books, an imprint of Simon & Schuster, Inc., 2021)
"On a snowy evening in March, thirty-something Noelle Butterby is on her way back from an event at her old college when disaster strikes. With a blizzard closing off roads, she finds herself stranded, alone in her car, without food, drink, or a working charger for her phone. All seems lost until Sam Attwood, a handsome American stranger also trapped in a nearby car, knocks on her window and offers assistance. What follows is eight perfect hours together, until morning arrives and the roads finally clear. The two strangers part, positive they'll never see each other again but fate, it seems, has a different plan. As the two keep serendipitously bumping into one another, they begin to realize that perhaps there truly is no such thing as coincidence."--Amazon.